2005
DOI: 10.1063/1.1898209
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Li, Ca, and Al with aromatic carbon materials: An ab initio study

Abstract: The interactions of benzene (C6H6), naphthalene (C10H8), and perinaphthene (C13H9) with metal atoms (Li, Ca, and Al) were studied using second-order Møller-Plesset perturbation theory. By analyzing the frontier molecular orbitals, geometric structures, binding energies, and charge transfers, it was found that these metal atoms can bond strongly with C13H9, but can only bond weakly with C6H6 and C10H8. The bonding nature between a metal atom and C13H9 at their ground state depends significantly on the valence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…The conclusion emerging from this test is that weak Cainteractions are considerably underestimated using the GGA͑PBE͒-DFT method. Related computational studies carried out by Sun et al 62 and Zhao et al 63 on Ca-doped aromatic hydrocarbon systems, showed similar underestimation of the electronic correlations using the GGA͑B3LYP͒-DFT method. An interesting question that raised while carrying out the present benchmark test was, is the Ca-C 24 H 12 system physically similar to Ca-decorated graphene?, or in other words, is it correct to extrapolate conclusions found in the Ca-C 24 H 12 system to Ca-decorated nanostructures?…”
Section: Computational Outline and Test Of The Methodssupporting
confidence: 56%
“…The conclusion emerging from this test is that weak Cainteractions are considerably underestimated using the GGA͑PBE͒-DFT method. Related computational studies carried out by Sun et al 62 and Zhao et al 63 on Ca-doped aromatic hydrocarbon systems, showed similar underestimation of the electronic correlations using the GGA͑B3LYP͒-DFT method. An interesting question that raised while carrying out the present benchmark test was, is the Ca-C 24 H 12 system physically similar to Ca-decorated graphene?, or in other words, is it correct to extrapolate conclusions found in the Ca-C 24 H 12 system to Ca-decorated nanostructures?…”
Section: Computational Outline and Test Of The Methodssupporting
confidence: 56%
“…54 A similar conclusion has been obtained by ab initio calculations for the Li-C 6 H 6 system. 55 These theoretical results support our expectation, although, to our knowledge, there is no theoretical report on the K -C 6 H 6 system.…”
Section: Formation and Thermal Stability Of K Clusterssupporting
confidence: 91%
“…Previous studies on the reactions of benzene with reactive metals have been performed in the condensed phase, in the gas phase, , and using matrix isolation. ,, Theoretical studies on these reactions have also been reported. ,,,, Collectively, this previous work documents reaction through an electron transfer pathway for isolated benzene molecules, and these studies have provided detailed information about the bonding in the metal–benzene complexes so formed. However, no previous work has addressed the details of this reaction chemistry for bulk solid-state benzene wherein proximity of multiple benzene molecules has the potential to alter the reaction pathway or the products formed.…”
Section: Introductionmentioning
confidence: 93%